دور الرقابة الشرعية في الحد من التحايل المحاسبي عند إعداد القوائم المالية من وجهة نظر موظفي مصرف الجمهورية - وكالة ترغلات - الزقوزي Mousa Altayeb (مجلة الاصالة, 2026)
This study investigates the role of Shariah supervision in reducing accounting fraud during the preparation of financial statements, focusing on the perceptions of employees at Jumhouria Bank – Taraghlat Branch. The research aims to evaluate the effectiveness of Shariah supervision as a governance mechanism that enhances transparency, strengthens internal control systems, and limits the misuse of accounting principles. A descriptive-analytical approach was employed, and data were collected through a structured questionnaire distributed to bank employees. Out of 35 distributed questionnaires, 27 valid responses were received, representing a response rate of 77.14%. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), applying descriptive statistics, reliability testing, and correlation analysis. The findings reveal that Shariah supervision plays a significant role in promoting ethical financial practices and ensuring compliance with Islamic principles. Respondents perceived a low level of accounting fraud within the institution, and a statistically significant negative correlation was found between Shariah supervision and accounting fraud. This confirms that stronger Shariah supervisory mechanisms contribute to reducing fraudulent financial practices and improving the integrity of financial reporting. The study concludes that Shariah supervision is a vital component of corporate governance in Islamic banking, reinforcing ethical accountability and transparency. It recommends